2004
DOI: 10.1081/ese-120027527
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Kuwait's Al-Qurain Landfill Using Remotely Sensed Data

Abstract: Kuwait's Al-Qurain landfill problem resulted from indiscriminate dumping of domestic and industrial waste in an abandoned quarry in the late 1970s and early 1980s. The landfill and surrounding areas were set aside for a government housing project without an environmental assessment of the impact of the landfill on the project. Inhabitants of the newly constructed housing area experienced persistent foul odor emanating from the landfill site. Since then, the issue has generated a lot of public interests, and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 1 publication
0
15
0
1
Order By: Relevance
“…Manzo et al (2016), através de diversos índices, entre eles de temperatura e vegetação, investigaram a influência antrópica de uso do solo após despejos de extração mineral no Parque Nacional Monte Vesuvius, na Itália. Kwarteng & Al-Enezi (2004), através de um levantamento temporal de imagens de médio e baixa resolução e seus índices, avaliaram um aterro não controlado no Kuwait, o qual causava problemas, desde um forte mau cheiro, até problemas de saúde pública devido à proximidade com habitações.…”
Section: Resultsunclassified
“…Manzo et al (2016), através de diversos índices, entre eles de temperatura e vegetação, investigaram a influência antrópica de uso do solo após despejos de extração mineral no Parque Nacional Monte Vesuvius, na Itália. Kwarteng & Al-Enezi (2004), através de um levantamento temporal de imagens de médio e baixa resolução e seus índices, avaliaram um aterro não controlado no Kuwait, o qual causava problemas, desde um forte mau cheiro, até problemas de saúde pública devido à proximidade com habitações.…”
Section: Resultsunclassified
“…This relative low number of publications should be linked to the local problem of OOMW disposal areas in the Mediterranean countries. Similar studies related either to the detection of uncontrolled landfills or to hazardous wastes [17][18][19][20][21] have shown the great potential of remote sensing to detect these sites. The synoptic view of overhead remote imaging can be very useful for the recognition and remediation of landfills and waste disposal areas.…”
Section: Introductionmentioning
confidence: 99%
“…Jones and Elgy determined that multispectral data could be used to monitor landfill gas migration and its effect on vegetation [33]. Kwarteng and Al-Enezi demonstrated that multispectral imagery could be used to monitor landfill development and its associated pollution profile [34].…”
Section: Multispectral Applicationsmentioning
confidence: 99%
“…Examples include the discovery and monitoring of underground fires at mines or landfills [115][116][117][118][119][120][121][122][123], the thermal characteristics of landfill processes [124,125], seeps or the release of leachate into the environment [126,127], or structural characteristics of landfill caps and other remediation methods [36,[128][129][130].…”
Section: Thermal Infrared Applicationsmentioning
confidence: 99%